Shifts in Intestinal Metabolic Profile Among Kidney Transplantation Recipients with Antibody-Mediated Rejection - Wang J; Zhang X; Li M; Li R; Zhao M (Dove Medical Press, 2023)
Junpeng Wang,1,2 Xiaofan Zhang,3 Mengjun Li,4 Ruoying Li,4 Ming Zhao1 1Department of Organ Transplantation, Zhujiang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 2Department of Urology, Henan Provincial People's Hospital, Zhengzhou University People's Hospital, Zhengzhou, People's Republic of China; 3Medical Research Center, The Second Affiliated Hospital of Zhengzhou University, Zhengzhou, People's Republic of China; 4Department of Pathophysiology, School of Basic Medical Sciences, Zhengzhou University, Zhengzhou, People's Republic of ChinaCorrespondence: Ming Zhao, Tel/Fax + 86 020 62782501, Email zhaoming02@hotmail.comBackground: Antibody-mediated rejection (AMR) is emerging as the main cause of graft loss after kidney transplantation. Our previous study revealed the gut microbiota alternation associated with AMR in kidney transplant recipients, which was predicted to affect the metabolism-related pathways.Methods: To further investigate the shifts in intestinal metabolic profile among kidney transplantation recipients with AMR, fecal samples from kidney transplant recipients and patients with end-stage renal disease (ESRD) were subjected to untargeted LC-MS-based metabolomics.Results: A total of 86 individuals were enrolled in this study, including 30 kidney transplantation recipients with AMR, 35 kidney transplant recipients with stable renal function (KT-SRF), and 21 participants with ESRD. Fecal metabolome in patients with ESRD and kidney transplantation recipients with KT-SRF were parallelly detected as controls. Our results demonstrated that intestinal metabolic profile of patients with AMR differed significantly from those with ESRD. A total of 172 and 25 differential metabolites were identified in the KT-AMR group, when compared with the ESRD group and the KT-SRF group, respectively, and 14 were common to the pairwise comparisons, some of which had good discriminative ability for AMR. KEGG pathway enrichment analysis demonstrated that the different metabolites between the KT-AMR and ESRD groups or between KT-AMR and KT-SRF groups were significantly enriched in 33 or 36 signaling pathways, respectively.Conclusion: From the metabolic point of view, our findings may provide key clues for developing effective diagnostic biomarkers and therapeutic targets for AMR after kidney transplantation.Keywords: antibody-mediated rejection, kidney transplantation, intestinal metabolic profile, LC-MS, end-stage renal disease